The Relationship between Emotional Maturity and Verbal Aggressive Behavior in State Vocational High School Students - Denissa, Marsyabilla Julia; Dasalinda, Dwi (research, training and philanthropy institution Natural Aceh, 2024)
This study aims to determine the relationship between emotional maturity and verbally aggressive behaviour in class XI students of SMKN 1 Anyer. The method used in this study was associative quantitative with a correlational approach, with a population of 360 students and a sample of 90 students using the Probability Sampling Technique, namely that each people has the same opportunity to be sampled without any sampling criteria. The data collection tool used is the questionnaire instrument. Test the hypothesis using the Product Moment From Pearson correlation test with a value of -.465, decision making with a significance value of 0.04 <0.05 is correlated or has a relationship. The calculation results show that there is a relationship between emotional maturity and verbally aggressive behaviour in class XI students of SMKN 1 Anyer in a negative direction or the opposite direction, the hypothesis is accepted Ha: (accepted) there is a significant relationship between emotional maturity and verbally aggressive behaviour in class XI students SMKN 1 Anye, Ho: (rejected) there is no relationship between emotional maturity and verbally aggressive behaviour in students of SMKN 1 Anyer, by concluding that the higher the level of emotional maturity, the lower the verbal aggressive behaviour, conversely, the higher the level of emotional maturity, the higher the verbal aggressive behaviour.